PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN BERTANYA SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS 3 DI MAN 1 MATARAM - Safitri, Sulistia; Wadi, Hairil; Suud, Suud; Wahidah, Ananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research aims to determine the application of the Think pair share learning model in class XI IPS 3 at MAN 1 Mataram. This research uses classroom action research with data collection techniques through observation, interviews and documentation. The stages of this research were carried out through initial observation, planning, action, observation and reflection. The subjects of this classroom action research were students of class XI IPS 3 MAN 1 Mataram, while the informants in the research were sociology subject teachers. The results of the first cycle of research showed that the level of students' problem solving abilities was (69%), asking questions (71%), and the teacher's application of the Think Pair Share model (75%). Furthermore, cycle II showed the level of problem solving ability (79%), asking ability (80%), and the teacher's application of the think pair share model (90%).